REPRESENTASI BULLYING DALAM FILM BETTER DAYS (Analisis Wacana Kritis Jager & Maier) - Ignasius Liliek Senaharjanta; Jeannifer Kairupan; Bernard Realino Danu Kristianto (Media Bina Ilmiah, 2025)
This study aims to determine the representation of bullying in the film Better Days (2019). Bullying is one of the social problems that is still concerning until now, especially in the realm of education. This phenomenon then became an inspiration for many filmmakers to raise this issue into a film, one of which was manifested in Better Days. This film is a Chinese film which tells a story of a high school girl who is bullied at her school when she is trying to cope with the pressures of competing for the college entrance exam. This study used a descriptive qualitative approach with Michel Foucault’s power relations theory and Jager & Maier’s Critical Discourse Analysis. Those methods used with the aim to see how bullying is potrayed through discursive practices (dialogue), non-discursive practices(action) , as well as the materialization of objects shown in the Better Days film. Based on the result, the study found that this film succeeded in presenting a depiction of bullying behavior in school through dialogue, actions, and objects.And not only the depiction of bullying behavior, but this film also goes deeper by showing that the existing bullying cases do not only revolve around the relationship between the perpetrator and the victim, but through out the process there are many factors and parties who also involve in the complexity of solving the bullying cases. Such as the police, parents, and the people themselves who are often indifferent.Until now the cases of bullying is still a problem that is often encountered. Therefore, the public is expected to be more sensitive to the bullying that occur around them as an initial effort to reduce the increase in existing cases